PENDAPINGAN MODEL LATIHAN DRILL SERVIS TENIS MEJA SISWA SMPSK REGINA PACIS BAJAWA - Maria Ermelinda Bela; Josep Marsianus Rewo (Jurnal Riset Pendidikan Multidisiplin dan Pengabdian Kepada Masyarakat, 2026)
Service skill is one of the fundamental techniques that plays an important role in table tennis performance. However, the service ability of junior high school students is still not optimal, indicating the need for an effective and structured training approach. This study aimed to analyze the effectiveness of mentoring through a drill training model in improving table tennis service skills of students at SMPSK Regina Pacis Bajawa. The study employed a descriptive quantitative approach with a training mentoring design. The research subjects were students who participated in table tennis learning or training activities. The mentoring program was implemented through structured and repetitive service drills accompanied by direct guidance and feedback. Data were collected using service skill tests, observations, and documentation, and then analyzed descriptively. The results showed an improvement in students’ table tennis service skills after the implementation of the drill-based mentoring model, particularly in terms of technical execution, service accuracy, and consistency. In addition, students demonstrated increased motivation and self-confidence during the training process. Therefore, mentoring through a drill training model is effective as a learning strategy to enhance table tennis service skills among junior high school students.